Analysis Of Scientific Works Conducted in the Literature on the Types of Tensioning Mechanisms in the Weaving Looms - F.A. Kozakov; D.G. Aliyeva; U.M. Ibrokhimov (Genius Journals, 2023)
In the weaving processes of the modern textile industry, the performance of the thread control mechanisms has a great impact on the quality of the fabric and the efficiency of the weaving process. This article presents an analysis of scientific works, articles and theses, and literature by experts and researchers related to the types and working order of tensioning mechanisms in various types of weaving looms, as well as warp and weft tensions.
Keywords: Weft thread; tension; tensioning mechanisms